PENGARUH TEKHNIK PIJAT ENDORPHIN UNTUK MENGURANGI NYERI PERSALINAN “KAJIAN LITERATUR”: THE INFLUENCE OF ENDORPHIN MASSAGE TECHNIQUE TO REDUCE LABOR PAIN: A LITERATURE REVIEW - Rosni Lubis; Zahra Nur Aprilia; Rosita Syarifah; Delmafainis; Nina Primasari; Mardeyanti (Jurnal Online Dengan Open Journal System, 2025)
Labor pain is generally intense, with only 2-4% of mothers experiencing mild pain during labor. Each mother in labor naturally experiences different levels of pain. Pain management during labor can be done pharmacologically or non-pharmacologically. Massage is one form of non-pharmacological treatment that can be performed, including Endorphin Massage. Mothers who receive endorphin massage experience a reduction in labor pain. Objective: To review the influence of Endorphin Massage as an alternative non-pharmacological therapy to reduce labor pain. Method: This study uses a literature review method by sourcing references from several indexed national and international journals. Results: Twelve articles indicate a significant relationship regarding the influence of endorphin massage techniques to reduce labor pain. This relationship is also influenced by other factors such as anxiety, labor history, birth companions, age, and education. Conclusion: It can be concluded that endorphin massage techniques can reduce labor pain.